2021
DOI: 10.3390/w13040398
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Characterization of the Vegetated Hydrodynamic System Using Non-Parametric Bayesian Networks

Abstract: The increasing risk of flooding requires obtaining generalized knowledge for the implementation of distinct and innovative intervention strategies, such as nature-based solutions. Inclusion of ecosystems in flood risk management has proven to be an adaptive strategy that achieves multiple benefits. However, obtaining generalizable quantitative information to increase the reliability of such interventions through experiments or numerical models can be expensive, laborious, or computationally demanding. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Similar studies considering storm surge and tidal currents have shown that mangroves can build the substrate and mitigate inland flooding over larger spatial scales (Furukawa et al, 1997;Mazda et al, 1997b;Krauss et al, 2009;Montgomery et al, 2018). Numerical simulations have further investigated wave interaction with vegetation by modeling separately energy dissipation terms and expanding analyses to conditions not observed in the field or physical models (Zhang et al, 2012;Guannel et al, 2015;Maza et al, 2015;Narayan et al, 2016;Chella et al, 2020;Niazi et al, 2021). Physical models investigating wave propagation through live vegetation (Ozeren et al, 2014) or vegetation mimics (Augustin et al, 2009;Anderson and Smith, 2014;Ozeren et al, 2014;Cox, 2015, 2016) have identified relationships between C D and parameters including the Reynolds number, Re, and Keulegan-Carpenter number, KC.…”
Section: Previous Studies Of Wave Height Attenuation Through Emergent Vegetationmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar studies considering storm surge and tidal currents have shown that mangroves can build the substrate and mitigate inland flooding over larger spatial scales (Furukawa et al, 1997;Mazda et al, 1997b;Krauss et al, 2009;Montgomery et al, 2018). Numerical simulations have further investigated wave interaction with vegetation by modeling separately energy dissipation terms and expanding analyses to conditions not observed in the field or physical models (Zhang et al, 2012;Guannel et al, 2015;Maza et al, 2015;Narayan et al, 2016;Chella et al, 2020;Niazi et al, 2021). Physical models investigating wave propagation through live vegetation (Ozeren et al, 2014) or vegetation mimics (Augustin et al, 2009;Anderson and Smith, 2014;Ozeren et al, 2014;Cox, 2015, 2016) have identified relationships between C D and parameters including the Reynolds number, Re, and Keulegan-Carpenter number, KC.…”
Section: Previous Studies Of Wave Height Attenuation Through Emergent Vegetationmentioning
confidence: 93%
“…Methods have been proposed to parameterize emergent vegetation including wetland plants (Feagin et al, 2011;Liu et al, 2021;Niazi et al, 2021) and specifically the trunk-prop root system of the Rhizophora genus (Ohira et al, 2013;Niazi et al, 2021). The model of Ohira et al (2013) was used as the basis of the design of the idealized mangrove tree for this study because it was the basis of previous laboratory studies (Maza et al, 2017(Maza et al, , 2019Tomiczek et al, 2020b) and an ongoing study at another laboratory (Tomiczek et al, 2021) and would facilitate comparisons of the results.…”
Section: Mangrove Specimenmentioning
confidence: 99%
“…The scene is set by a review paper that defines coastal resilience, claiming that Building with Nature approaches are intrinsic to achieving resilience [1]. All authors concur that nature-based solutions provide a means of meeting nature restoration goals as well as addressing socio-economic needs [1][2][3][4][5][6][7][8][9][10][11][12][13]. While one article evaluates the cost effectiveness of a particular solution [6], a critically reflective article compares nature-based solutions with conventional engineering solutions, distinguishing four axes, two of which relate to the inclusion of multiple stakeholders and ecological knowledge [5].…”
mentioning
confidence: 99%
“…The majority of articles echo the need for both engineering and ecological knowledge in the design process, and two actively involve stakeholders in their analyses [11,13]. There are six articles that include the design of a (hybrid) nature-based solution [2,4,6,9,10,13], while five articles undertake interdisciplinary experiments and measurements in the laboratory, the field, or via modeling to ascertain the performance of nature-based solutions [2,3,[7][8][9]. A number of contributions focus on environmentally friendly Integrated Coastal Management (ICM), with two articles identifying factors most beneficial to ICM [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation